Managing Islamic School Culture to Develop Students’ Religious Character - Hadi, Mokhamad Yaurizqika; Prayogi, Dini Siamika Tito (Journal of Educational Research and Practice, 2025)
Religious culture-based management in educational institutions plays a crucial role in forming students' character by integrating Islamic values into daily practices. However, many current approaches lack a holistic synthesis between managerial systems and religious cultural development. This study aims to systematically analyze how religious culture management aligns with character education in a comprehensive and structured manner. Employing a qualitative design through a Systematic Literature Review (SLR), the data were drawn from journal articles, books, and theses indexed in Google Scholar, DOAJ, and Sinta databases, spanning the years 2013 to 2024, with inclusion criteria focusing on Islamic education, school management, and character development. Key findings indicate that 76% of sources emphasized the role of school leaders in integrating religious values, 68% reported positive impacts of habituation strategies such as group prayer and Qur’anic recitation, and 63% highlighted the importance of teacher modeling and parent-community collaboration. Concrete implementation is visible in school policies, curricular integration, extracurricular activities, and symbolic religious environments. These findings offer practical guidance for policymakers and educators to construct culturally-aligned, ethically-driven education systems that support the holistic formation of students' intellectual, moral, and spiritual identity in line with national character goals.